Humanistic care and nurse-patient communication in the nursing clinic (护理门诊人文关怀和护患沟通技巧浅谈) - LIU Dan (刘丹) (Association of Integrative Nursing, 2022)
The nursing outpatient clinic is the crucial part of current medical and healthcare service. In order to improve the overall quality of nursing service provided in the outpatient clinic, efforts should be made to improve the nurses' awareness of humanistic care their skills of communicating with patients. This paper briefly discussed the factors influencing the mental status of outpatients and potential reasons of nurse-patient dispute, and summarized the measures of humanistic care and nurse-patient communication, in order to provide reference for the quality improvement of nursing service in the outpatient clinic. (护理门诊是当前医疗卫生服务体系中的重要一环, 为保证护理门诊的整体护理质量, 应进一步提高人文关怀认识, 强化人文关怀措施并保持妥善的护患沟通技巧。本文主要介绍了门诊患者的心理状态和导致护患纠纷的相关因素, 并对目前临床常见的人文关怀和护患沟通技巧进行总结, 以期为进一步提升门诊护理服务质量提供参考。)